Illegal Investment Crimes in the Perspective of Anomie Theory - Ananda Putri S. Maksum; Weny Almoravid Dungga; Mellisa Towadi (Estudiante Law Journal, 2022)
This study aims to analyze criminological reviews based on the theory of anomie criminal acts of fraud (Illegal Investment) and law enforcement of criminal acts of fraud in the Gorontalo Regional Police. This study uses the Normative - Empirical method. By using primary data and secondary data, data collection techniques through interviews, observation, and literature studies. The results of this study indicate the causes of people becoming perpetrators of illegal investment fraud, namely wanting to enrich themselves, and taking advantage of opportunities for the lack of public knowledge about the mechanisms and ways of working investment products and the general public. Factors that lead to criminal acts of illegal investment: Economic, environmental, and social factors Investing in Indonesia is regulated in Law no. 25 of 2007 concerning Investment. Law enforcement by the Gorontalo Regional Police general criminal investigation cyber investigation process through complaints of victims of illegal investments. To obtain the identity of the perpetrator, and the role of the perpetrator in the implementation of investment fraud crimped es, an investigation process is carried out up to the final stage of the legal process.